Metal‐Free Direct Oxidative C−N Bond Coupling of Quinoxalin‐2(1H)‐ones with Azoles under Mild Conditions. Issue 15 (21st April 2021) - Guo, Jingwen; Zhang, Lina; Du, Xinyue; Zhang, Liting; Cai, Yuepiao; Xia, Qinqin
Abstract: Direct C3−H amination of quinoxalin‐2(1 H )‐ones with azoles under mild conditions promoted by PIFA has been achieved in good yield in a very fast manner. Mechanistic study revealed that the reaction proceeds through a radical process. In addition, this method could be applied to gram‐scale reaction. Abstract : Direct C3−H amination of quinoxalin‐2(1 H )‐ones with azoles has been achieved in a very fast manner. This protocol features broad substrate scope, good yields, and mild reaction conditions.